Pengabdian Masyarakat: Waspada Phishing bagi Kalangan Pelajar - Melda Agnes Manuhutu; Imanuela Daharang; Sindi Sindi; Goklas Goklas; Marcello Marcello; Alberthus Alberthus; Orulin Orulin (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Cybercrime threats in the form of Phishing continue to rise, with students being one of the most vulnerable groups. Based on BSSN 2023 data, over 403 million cyber traffic anomalies were recorded in Indonesia, with Phishing as the most frequent cybercrime mode. This community service activity aimed to improve the digital security literacy of SMP Negeri 1 Kabupaten Sorong students through an interactively designed, practice-based education program. The method used was Participatory Learning with four stages: interactive socialization, practical anti-Phishing training, cybersecurity technology application, and continuous evaluation and mentoring. Results showed significant improvement in participants' ability to identify Phishing characteristics, distinguish genuine websites from fake ones, and understand digital account protection measures. The simulation-based and real case study approach proved effective in increasing active student engagement. The success of this program is expected to serve as a model for cybersecurity education activities in other schools in the West Papua region.